2021
DOI: 10.1093/aje/kwab045
|View full text |Cite
|
Sign up to set email alerts
|

Transporting Subgroup Analyses of Randomized Controlled Trials for Planning Implementation of New Interventions

Abstract: Subgroup analyses of randomized controlled trials guide resource allocation and implementation of new interventions by identifying groups of individuals who are likely to benefit most from the intervention. Unfortunately, trial populations are rarely representative of the target populations of public health or clinical interest; unless the relevant differences between trial and target populations are accounted for, subgroup results from trials might not reflect which groups in the target population will benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…We have provided estimates of statistical heterogeneity of effect, which appeared predominantly due to heterogeneity of setting and with context-specific details provided in data tables. This heterogeneity may make it more challenging for implementers to select context-relevant evidence; future reviews may consider making use of context heterogeneity present across trials to be informative using transportability principles [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have provided estimates of statistical heterogeneity of effect, which appeared predominantly due to heterogeneity of setting and with context-specific details provided in data tables. This heterogeneity may make it more challenging for implementers to select context-relevant evidence; future reviews may consider making use of context heterogeneity present across trials to be informative using transportability principles [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this particular case, the per-protocol effect may arguably be more transportable to other populations or contexts, depending on whether the degree and type of nonadherence would be comparable across other settings. The per-protocol effect may also more closely align in definition with some of the likely implementation strategies posttrial (since nonadherence due to the trial-specific paperwork would be a nonissue) ( 9 ). However, estimating the per-protocol effect requires strong unverifiable assumptions.…”
Section: Making the Most Of The Randomized Trials We Can Conductmentioning
confidence: 99%
“…Ultimately, the effort to collect rich data in a trial setting can serve as an opportunity to estimate the adapted interventions of treatment strategies beyond those that defined the original trial’s protocol. Note that such data collection requires forethought and at minimum needs to include assessments of the anticipated adapted intervention definitions and associated confounders ( 9 , 15 , 16 ).…”
Section: Making the Most Of The Randomized Trials We Can Conductmentioning
confidence: 99%
See 1 more Smart Citation
“…For considerations of daily oral PrEP among MSM, transportability analyses have been used to extrapolate findings from randomized trials to new populations [21 ▪ ]. For example, a recent manuscript found that by accounting for differences in gender identity, condomless receptive anal intercourse, and primary sexual role (top, bottom, versatile), we can transport estimates from the iPrEx trial on PrEP effectiveness conducted in six countries in North and South America, Asia, and Africa to population subgroups in San Francisco and Chicago [21 ▪ ].…”
Section: Review Of the Literaturementioning
confidence: 99%